Time Perception and the Experience of Time When Immersed in an Altered Sensory Environment - Glicksohn, Joseph; Berkovich-Ohana, Aviva; Mauro, Federica; Ben-Soussan, Tal D. (Frontiers in Human Neuroscience, 2017)
The notion that exposure to a monotonous sensory environment could elicit reports indicating aberrant subjective experience and altered time perception is the impetus for the present report. Research has looked at the influence of exposure to such environments on time perception, reporting that the greater the environmental variation, the shorter is the time estimation obtained by the method of production. Most conditions for creating an altered sensory environment, however, have not facilitated an immersive experience, one that directly impacts both time perception and subjective experience. In this study, we invited our participants to enter a whole-body altered sensory environment for a 20-minute session, wherein they were asked to relax without falling asleep. The session included white-colored illumination of the chamber with eyes closed (5 min), followed by 10 minutes of illuminating the room with color, after which a short report of subjective experience was collected using a brief questionnaire; this was followed by an additional 5 min of immersion in white light with closed eyes. The participants were then interviewed regarding their subjective experience, including their experience of time within the chamber. Prior to entering the chamber, the participants completed a time-production task. One group of participants then repeated the task within the chamber, at the end of the session; a second group of participants repeated the task after exiting the chamber. We shall report on changes in time production, and present data indicating that when produced time is plotted as a function of target duration, using a log-log plot, the major influence of sensory environment is on the intercept of the psychophysical function. We shall further present data indicating that for those participants reporting a marked change in time experience, such as “the sensation of time disappeared”, their time-production data could not be linearized using a log-log plot, hence indicating that for these individuals there might be a ‘break’ in the psychophysical function.